Study on the shear characteristics and macro scopic mechanism of rock joints under cyclic loading conditions - WANG Gang; SONG Qi; WANG Pengju; WU Xuezhen; ZHANG Yeqiang; DUAN Rongmei (矿业科学学报)
Under cyclic load conditions, rock mass engineering such as tunnels and underground storage is prone to large deformation and collapse due to the gradual deterioration of surrounding rock performance. It is of great significance to study the shear characteristics of rock joints and macro-mesoscopic mechanism for evaluating the service safety of rock mass engineering under cyclic load conditions. Joint specimens were prepared with high strength gypsum, cyclic shear tests were carried out under constant normal load, and the numerical simulation method of finite element and discrete element coupling was used. The results show that the greater the roughness of joint surface, the greater the peak shear strength. In the same number of cycles, the peak shear strength decreases with the increase of cyclic shear displacement. The average dilatancy angle decreases with the increase of the number of cycles. In the same number of cycles, the average dilatancy angle decreases with the increase of cyclic shear displacement and increases with the increase of joint roughness. With the progress of cyclic shear, the stress evolution tends to be stable, and the number of cracks decreases with the increase of cyclic shear cycles.